Crystallization and X-ray diffraction analysis of the DNA-remodelling protein DnaD from Bacillus subtilis. - Schneider, S; Carneiro, M; Ioannou, C; Soultanas, P; Paoli, M (2007)
The DnaD protein is an essential component of the chromosome-replication machinery of the Gram-positive bacterium Bacillus subtilis and is part of the primosomal cascade that ultimately loads the replicative ring helicase DnaC onto DNA. Moreover, DnaD is a global regulator of DNA architecture, as it forms higher order nucleoprotein structures in order to open supercoiled DNA. Here, the crystallization and preliminary X-ray diffraction analysis of the two domains of DnaD from B. subtilis are reported. Crystals of the N-terminal domain are trigonal, with either P3(1)21 or P3(2)21 space-group symmetry, and diffracted X-rays to 2.0 A resolution; crystals of the C-terminal domain are hexagonal, with space group P6(1) or P6(5), and diffracted X-rays to 2.9 A resolution in-house. Determination of the structure of the DnaD domains will provide insight into how remodelling of the nucleoid is associated with priming of replication in the model Gram-positive organism B. subtilis.